A pooled analysis of the safety of tofacitinib as monotherapy or in combination with background conventional synthetic disease-modifying antirheumatic drugs in a Phase 3 rheumatoid arthritis population - Kivitz, Alan J.; Cohen, Stanley; Keystone, Edward; van Vollenhoven, Ronald F.; Haraoui, Boulos; Kaine, Jeffrey; Fan, Haiyun; Connell, Carol A.; Bananis, Eustratios; Takiya, Liza; Fleischmann, Roy (Seminars in arthritis and rheumatism, 2018)
This post-hoc, pooled analysis of Phase 3 studies of tofacitinib examined the safety of tofacitinib 5 and 10 mg twice daily (BID) when used as monotherapy versus combination therapy with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) in patients with rheumatoid arthritis (RA). Pooled data from six double-blind, randomized controlled Phase 3 studies of tofacitinib 5 and 10 mg BID in patients with RA were analyzed for safety and stratified by administration as monotherapy (ORAL Solo: NCT00814307 and ORAL Start: NCT01039688) or in combination with csDMARDs (ORAL Sync: NCT00856544, ORAL Standard: NCT00853385, ORAL Scan: NCT00847613, and ORAL Step: NCT00960440), and by glucocorticoid use at baseline. Safety assessments included incidence rates (IRs) for serious adverse events (SAEs), discontinuations due to AEs, serious infection events, and herpes zoster (HZ), and were evaluated throughout the duration of the Phase 3 studies. In total, 3881 patients were included in the safety analysis (monotherapy studies: n = 1380; combination therapy studies: n = 2501). IRs for selected AEs of interest were generally numerically lower in patients who received tofacitinib 5 and 10 mg BID as monotherapy than as combination therapy (SAEs: IR [range] 6.21–6.72 versus IR 10.17–13.46; discontinuations due to AEs: IR 5.53–6.18 versus IR 10.80–11.01; serious infections: IR 1.57–1.66 versus IR 3.39–3.56; HZ: IR 1.95–2.93 versus IR 4.37–4.99, respectively), irrespective of tofacitinib dose or glucocorticoid use. There were too few patients and events within the placebo group to fully evaluate effect between combination therapy and monotherapy. Safety profiles were generally similar between patients receiving monotherapy and combination therapy; however, selected safety events of interest, including HZ and serious infections, showed lower IRs with non-overlapping 95% confidence intervals for tofacitinib all monotherapy versus combination therapy. Tofacitinib monotherapy may, therefore, have fewer safety events compared with combination therapy, and have a favorable risk-benefit profile in patients with active RA who are intolerant to csDMARDs.